Investigation and Comparison of the Enrichment Potential of Turkey (Şenkaya, Erzurum) Coals with Knelson Concentrator - Oyku Bilgin (Advances in Materials Science and Engineering)
The quality of coals from, Erzurum varies widely. Two coal samples from this area were compared. The first has a composition of 19% ash, 5700 kcal, and 3% sulfur while the other has 49.20% ash, 3000 kcal, and 1.6% sulfur composition. It is understood that the first coal sample is a high-quality coal. Although the ash content of the second coal sample is determined to be high and the calorie value is low, the low sulfur content is advantageous for the environment. This study aimed at increasing the quality of coal samples by carrying out experiments for reducing the ratio of ash and sulfur with Knelson’s enrichment processes. Chemical analysis, sieve analysis experiments, %ash, %moisture, and %calorie values of each fraction are determined from two different C1 and C2 coal samples taken from the Balkaya village belonging to Şenkaya, Erzurum. Then, %ash, %yield, and %sulfur analyzes were carried out on the coal samples using the Knelson gravity separator enrichment method, and the results were evaluated for coal samples.